Janus hydrogel patch composed of protein and polypeptide and preparation method of Janus hydrogel patch
By using Janus hydrogel patches composed of gelatin, negatively charged modified zein, polylysine and jenipine, the existing biological patches have poor adhesion and strong immune response, and the effect of stable adhesion and avoiding adhesion in the bodily fluid environment is achieved, and good biocompatibility and mechanical properties are also achieved.
Patent Information
- Application Number
- CN202510002078.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
AI Technical Summary
In clinical applications, existing biological patches have problems such as poor adhesion of wet tissue, strong immune response, and easy adhesion after surgery, which is difficult to meet clinical needs.
A hydrogel patch with a bilateral structure is formed using a Janus hydrogel patch composed of gelatin, negatively charged modified zein, polylysine and jenipine.
It has achieved stable single-sided adhesion ability in the body fluid environment, avoiding adhesion with surrounding tissues, and has good biocompatibility, degradability, high mechanical strength and strain ability.
Smart Images

Figure CN119746175A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material chemistry, in particular to a Janus hydrogel patch composed of protein and polypeptide and a preparation method thereof. Background Art
[0002] The emergence of biological patches has set off a major revolution in the medical field. Its good mechanical properties have made it widely used in tissue damage repair and wound closure in the body, such as abdominal wall defect repair, hernia repair, heart repair, vascular reconstruction and other fields (Velasco VF, Velastegui L J. Advances and results in omental patch repair of gastrointestinal perforations: A narrative review [J]. Surgery in Practice and Science, 2024, 19100261-100261.). The biological patches currently used in clinical surgery mainly include biological tissue patches taken from animals (such as bovine pericardium patches, porcine small intestinal mucosal patches, etc.) and chemically synthesized polymer patches (such as polypropylene, polytetrafluoroethylene, etc.). Most of these materials are patches that do not have tissue adhesion. When used clinically, surgeons need to suture and fix the patches to the target surgical area with sutures, which not only increases the doctor's clinical operation time and workload, but also brings great pain to patients. In addition, biological tissue patches taken from animals are very likely to cause immune rejection in the body. Chemically synthesized polymer patches have poor degradability and are prone to cause adverse consequences such as adhesion to surrounding tissues (Rowshan TK, Athanasios T, Harmit G, et al. Synthetic versus Biological Patches for CDH: A Comparison of Recurrence Rates and Adverse Events, Systematic Review, and Meta-Analysis. [J]. European journal of pediatric surgery, 2022, 33 (3):).
[0003] Therefore, the development of biological patches with reliable wet tissue adhesion, low immunogenicity, anti-postoperative adhesion, high biosafety, and degradability in body fluid environments is not only an urgent need for clinical applications but also an important development direction for basic research. At present, biological patches in the basic research stage are mainly Janus hydrogels formed by synthetic polymers (such as polyvinyl alcohol and polyethylene glycol) and chemically modified natural polymers (such as catechol-modified chitosan, hyaluronic acid and cellulose). Although the Janus hydrogel patch prepared by the above materials has high mechanical modulus, strain capacity and the characteristics of preventing adhesion after surgery, it still has the disadvantages of poor wet adhesion, relatively complex preparation, potential biological toxicity, long degradation cycle or non-degradability (Weiwen L, Wenyi H, Rongkang H, et al. Peritoneum-inspired Janus Porous Hydrogel with Anti-deformation, Anti-adhesion and Pro-healing Characteristics for Abdominal Wall Defect Treatment. [J]. Advanced materials, 2022, 34 (15): e2108992-e2108992.). Compared with synthetic polymers or modified natural polymers, natural or recombinant proteins have excellent performance in degradability and biocompatibility, and are ideal biological patch materials. However, the protein hydrogel patches reported currently mainly face the problems of high cost, poor wet tissue adhesion, and easy adhesion after surgery, which are difficult to meet actual clinical needs.
[0004] Therefore, developing a protein hydrogel patch with low cost, reliable tissue adhesion and postoperative anti-adhesion is a technical problem that technicians in this field urgently need to solve. Summary of the invention
[0005] In view of this, the present invention provides a Janus hydrogel patch composed of protein and polypeptide and a preparation method thereof. The Janus hydrogel patch of the present invention is prepared from gelatin, negatively charged modified corn protein, polylysine and genipin. The Janus hydrogel patch has a double-sided structure, one side of which is a hydrogel substrate layer and the other side is an adhesion layer. The Janus hydrogel patch of the present invention has the advantages of good biosafety, good degradability, and high wet tissue adhesion strength. The Janus structural design enables one side of the hydrogel patch to have strong tissue adhesion, while the other side has the characteristics of anti-tissue adhesion, so that stable adhesion to the target tissue and organ can be achieved in a body fluid environment, while avoiding adhesion to surrounding tissues.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A Janus hydrogel patch composed of protein and peptide, which has a substrate layer and an adhesive layer from bottom to top;
[0008] The substrate layer is formed by mixing and stirring a negatively charged modified corn protein solution and a gelatin aqueous solution to form a mixed solution through electrostatic and / or hydrogen bonding, and then covalently cross-linking and assembling genipin powder;
[0009] The adhesive layer is formed by spraying polylysine aqueous solution, negatively charged modified corn protein solution and genipin aqueous solution in sequence and in equal volumes layer by layer for 6-8 times through electrostatic and / or hydrogen bonding covalent cross-linking;
[0010] The substrate layer and the adhesive layer are bonded by electrostatic and hydrogen bonds between the corn protein solution, the gelatin aqueous solution and the polylysine aqueous solution, and are stably bonded by covalent cross-linking assembly through the genipin aqueous solution.
[0011] Furthermore, the relative molecular mass of the polylysine is 3000-4000 kD.
[0012] Furthermore, the mass concentration of gelatin in the gelatin aqueous solution is 10-150 mg / ml; the mass concentration of corn protein in the negatively charged modified corn protein solution is 10-150 mg / ml; the mass concentration of polylysine in the polylysine aqueous solution is 1.28-64 mg / ml; the mass concentration of genipin in the genipin aqueous solution is 0.25-1.25 mg / ml.
[0013] Furthermore, the volume ratio of the negatively charged modified corn protein solution to the gelatin aqueous solution in the substrate layer is 1:3, and the amount of genipin used is 0.2-2% of the mass fraction of the mixed solution.
[0014] The present invention also provides a method for preparing the Janus hydrogel patch composed of protein and peptide, comprising the following steps:
[0015] (1) mixing the genipin aqueous solution, gelatin aqueous solution, and negatively charged modified corn protein solution in the substrate layer in proportion, heating and stirring until a blue viscous liquid is formed and casting into a mold, and cooling naturally at room temperature to obtain a hydrogel substrate layer;
[0016] (2) The polylysine aqueous solution, the negatively charged modified zein aqueous solution, and the genipin aqueous solution in the adhesion layer are sprayed layer by layer alternately onto one side of the substrate layer prepared in step (1) to obtain a Janus structure hydrogel patch.
[0017] Furthermore, the preparation method of the negatively charged modified corn protein solution in step (1) is: adding corn protein to an aqueous solution of sodium dodecyl sulfate to obtain a negatively charged modified corn protein aqueous solution.
[0018] The preparation method of the polylysine aqueous solution is as follows: dissolving polylysine in double distilled water to obtain the polylysine aqueous solution;
[0019] The preparation method of the gelatin aqueous solution is as follows: dissolving gelatin in double distilled water to obtain the gelatin aqueous solution;
[0020] The preparation method of the genipin aqueous solution is as follows: dissolving genipin in double distilled water to obtain the genipin aqueous solution;
[0021] The stirring in step (1) is magnetic stirring, the stirring temperature is 20-80° C., the stirring time is 10-60 min, and the magnetic stirring speed is 100-800 r / min.
[0022] Furthermore, in step (2), the pH values of the polylysine aqueous solution and the negatively charged modified zein aqueous solution are first adjusted to 5.0-8.0, and then the adhesion layer is prepared.
[0023] The beneficial effects of the present invention are as follows: the Janus hydrogel patch prepared by using gelatin, negatively charged modified corn protein, polylysine and genipin as raw materials has stable one-sided adhesion ability in an aqueous environment, and no adhesion on the other side, and has good biocompatibility, degradability, high mechanical strength and deformability. The strain of the Janus hydrogel patch of the present invention can reach 150-200%, and after 20 cycles of tensile testing at 100% strain, there is no obvious lag in the strain performance. The Young's modulus of the Janus hydrogel patch of the present invention is about 70kPa. When the hydrogel patch of the present invention adheres to wet pig skin tissue, it first forms an initial adhesion with the surface of the pig skin tissue through non-covalent bonds. At this time, the interfacial peeling energy measured by the 180° peeling test is 36J / m 2 As time goes by, the genipin in the adhesive layer of the Janus hydrogel patch can further form a covalent bond with the surface of the pig skin tissue, further improving the tissue adhesion strength. After the Janus hydrogel patch of the present invention adheres to the surface of the pig skin tissue for 24 hours, the interfacial peeling energy measured by the 180° peeling test can reach 150 J / m 2 The Janus hydrogel patch of the present invention can be used for underwater adhesion on different substrates, such as metal, plastic, glass, rubber, wood and other different substrates, as well as different organs such as heart, liver, spleen, lung, kidney and other different organs. The Janus hydrogel patch of the present invention can be freeze-dried for storage, and the freeze-dried patch can be placed in a water environment to reform a single-sided adhered Janus hydrogel patch, which has the characteristics of being storable, sticky when exposed to water, simple to operate, and convenient to use.
[0024] The preparation method of the Janus hydrogel patch of the present invention is simple, rapid, does not require expensive equipment, is green, environmentally friendly, and has strong operability. The negatively charged modified corn protein and the positively charged gelatin and polylysine are combined at the interface between the hydrogel substrate layer and the adhesion layer of the Janus hydrogel patch through electrostatic, hydrogen bonding and covalent crosslinking mediated by genipin to form a stable Janus structure. The covalent bonds mediated by genipin in the hydrogel patch also provide the hydrogel patch with good mechanical strength and strain capacity. The sulfate group and amino group on the surface of the adhesion layer of the Janus hydrogel patch are also conducive to electrostatic bonding with the amino group and carboxyl group on the surface of the biological tissue, and the genipin on the surface of the adhesion layer and the amino group on the surface of the biological tissue are crosslinked by covalent bonds to form stable adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 An optical picture of the Janus hydrogel patch provided by the present invention;
[0026] Figure 2 The digital photos of the Janus hydrogel patch provided by the present invention with a weight adhered to one side underwater include A (the case where a 20-gram weight is adhered to the hydrogel substrate layer of the Janus hydrogel patch) and B (the case where a 20-gram weight is adhered to the adhesive layer of the Janus hydrogel patch).
[0027] Figure 3 The Janus hydrogel patch provided by the present invention has single-sided adhesion performance to different substrates and biological tissues in a water environment (25°C).
[0028] Figure 4 The force curve of the Janus hydrogel patch provided by the present invention after being adhered to the wet pig skin surface and subjected to a 180° peel test, including the force curve of the peel test immediately after adhesion and the peel test after adhesion for 24 hours;
[0029] Figure 5 The stress-strain curve (a) and Young's modulus (b) of the Janus hydrogel patch provided by the present invention measured at a constant tensile rate of 50 mm / min at 25°C.
[0030] Figure 6 The present invention provides a Janus hydrogel patch which is subjected to 20 cycles of stretching at 25° C. with a constant tensile strain of 100% and a constant stretching rate of 50 mm / min, and a stress-strain curve.
[0031] Figure 7 The optical photograph of the freeze-dried Janus hydrogel patch provided by the present invention (a), the optical photograph of the freeze-dried patch after being immersed in 37°C phosphate buffered saline (PBS) for 5 minutes after being stored for 2 weeks (b), and the peeling test curve after adhering to the wet pig skin surface for 24 hours (c);
[0032] Figure 8 The optical density results (a) of the extracts of the Janus hydrogel patches with different mass concentrations provided by the present invention after co-culture with 3T3 fibroblasts for 24 hours, and the confocal fluorescence microscope images (b) of the saturated extracts of the Janus hydrogel patches with 100% mass concentration after co-culture with 3T3 fibroblasts for 24, 48, and 72 hours. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] 750 mg of zein was dispersed in 10 ml of 150 mM sodium dodecyl sulfate (SDS) aqueous solution, and ultrasonicated at 25°C for 30 min to obtain a negatively charged zein solution. The pH of the negatively charged zein solution was adjusted to 7.0 using a 5 mM NaOH aqueous solution.
[0036] 225 mg of type A gelatin was dissolved in 3 ml of double distilled water, and ultrasonicated at 45°C for 30 min to obtain a 75 mg / ml gelatin aqueous solution. The pH of the gelatin solution was adjusted to 6.0 with a 5 mM NaOH aqueous solution.
[0037] 384 mg of polylysine was dissolved in 10 ml of double distilled water, and vortexed at 25° C. until completely dissolved to obtain a 38.4 mg / ml polylysine aqueous solution, and the pH of the polylysine aqueous solution was adjusted to 7.0 with a 5 mM NaOH aqueous solution.
[0038] Dissolve 10 mg of genipin in 10 ml of double distilled water, vortex and sonicate at 25° C. for 30 min to obtain a 1 mg / ml genipin aqueous solution, and adjust the pH of the genipin aqueous solution to 7.0 with a 5 mM NaOH aqueous solution.
[0039] Preparation of Janus hydrogel patch: 1 ml of negatively charged modified corn protein aqueous solution was added to 3 mL of gelatin aqueous solution and mixed evenly. 3.6 mg of genipin powder was added to the mixture and stirred at 70°C for 30 min to prepare a blue viscous liquid. The viscous liquid was poured into a polytetrafluoroethylene mold and cooled to 25°C to obtain a hydrogel substrate layer composed of gelatin, corn protein and genipin.
[0040] The prepared polylysine aqueous solution, negatively charged modified zein aqueous solution and genipin aqueous solution were alternately sprayed on the surface of the zein-gelatin-genipin hydrogel substrate layer obtained above, and the volume of the solution sprayed each time was 0.5 mL. After each solution was sprayed, it was necessary to stay on the substrate surface for 2-3 minutes, then rinsed with double distilled water, and dried with nitrogen gas before spraying the next solution. Repeat the above spraying and rinsing steps, and after 8 cycles of alternate spraying, the Janus hydrogel patch ( Figure 1 ).
[0041] Test Example 1 Underwater Adhesion Performance of Janus Hydrogel Patch
[0042] The Janus hydrogel patch was vertically hung in a container filled with double distilled water, and weights were attached to both sides of the Janus hydrogel patch to test its single-sided adhesion ability. Figure 2 As shown in the figure, the substrate layer of the Janus hydrogel patch cannot adhere to the weight, while the adhesive layer on the other side can effectively adhere to the weight, indicating that the obtained Janus hydrogel patch has single-sided adhesion ability, showing the potential to avoid adhesion to surrounding tissues when used in a wet environment of a biological body. In addition, we further evaluated the underwater adhesion ability of the adhesive layer of the Janus hydrogel patch to different solid substrates and tissue surfaces (including metal, plastic, glass, rubber, wood, as well as the heart, liver, spleen, lungs, and kidneys of animals). Figure 3 As shown, the Janus hydrogel patch can achieve effective adhesion to different substrates and tissues in water.
[0043] Experimental Example 2: Tensile test and cyclic tensile test of Janus hydrogel patch
[0044] A Janus hydrogel patch with a width of 10 mm and a thickness of 1 mm was prepared, and the hydrogel sample was subjected to a tensile test at 25°C using a universal testing machine equipped with a 100-N load sensor. The test speed was 50 mm / min, and the strain-stress data obtained were analyzed using KJ-1065A software. The tensile strain was set to 100%, and the Janus hydrogel material was subjected to 20 cyclic tensile tests to test the strain reversibility of the Janus hydrogel material.
[0045] Mechanical property test of Janus hydrogel patch: A Janus hydrogel patch with a length of 50 mm, a width of 10 mm, and a thickness of 1 mm was prepared by casting into a mold, and the Janus hydrogel patch was subjected to a tensile test at 25°C using a universal testing machine at a tensile rate of 50 mm / min. The strain of the Janus hydrogel patch was 109.42±14.35% ( Figure 5 a), and the Young's modulus was 65.63±9.45 kPa (Fig. b). Subsequently, the Janus hydrogel patch was subjected to cyclic stretching at 25°C with a constant tensile strain of 100% and a constant stretching rate of 50 mm / min to evaluate its reversibility of stretching. Figure 6 As shown in the figure, in 20 cycles of stretching, except for a small amount of elongation after the first stretching, the hysteresis loop area of the stress-strain curve of the Janus hydrogel is small in the subsequent cyclic stretching process, which indicates that the Janus hydrogel patch can have good deformation reversibility in a larger strain range.
[0046] Test Example 3 Peel Strength Test of Janus Hydrogel Patch
[0047] First, prepare a Janus hydrogel patch with a length of 50 mm, a width of 10 mm, and a thickness of 1 mm. Secondly, adhere the adhesive layer of the Janus hydrogel patch to the surface of wet pigskin tissue and press it with a pressure of 10 kPa. After the patch is in full contact with the pigskin, spread the pigskin flat and fix it on the sample table of the tensile tester. At 25°C, the peeling speed is constant at 50 mm / min. Peel the Janus hydrogel patch 180° in a direction parallel to the pigskin surface, and measure the real-time peeling curve. According to the formula: Adhesion work = peeling force / patch width, calculate the peel strength (J / m 2 ).
[0048] Peel strength of Janus hydrogel patch on wet pig skin tissue: A Janus hydrogel patch with a length of 50 mm, a width of 10 mm, and a thickness of 1 mm was prepared by casting into a mold. The adhesive layer of the Janus hydrogel patch was adhered to the surface of the soaked pig skin tissue, and then the pig skin was flattened and fixed on the sample table of the tensile tester. At a temperature of 25°C and a peeling speed of 50 mm / min, the Janus hydrogel patch was peeled 180° in a direction parallel to the pig skin surface, and the real-time peeling force curve was measured. According to the formula: Adhesion work = peeling force / patch width, the peel strength of the Janus hydrogel patch on the pig skin tissue (J / m 2 ). This method was used to measure the peel strength of the Janus hydrogel patch immediately after adhesion and after 24 hours of adhesion. Figure 4As shown in Figure 2, the immediate peel strength of the Janus hydrogel patch on pig skin tissue was 34.97±1.22 J / m 2 The peel strength after 24 hours of adhesion is 139.41±23.39J / m 2 This indicates that the Janus hydrogel patch has good wet adhesion to biological tissues after 24 hours.
[0049] Experimental Example 4 Dry storage and water-adhesive properties of Janus hydrogel patch
[0050] The prepared Janus hydrogel patch was placed in a freeze dryer at -80°C for vacuum freeze drying. Figure 7 a) Can be stored for a long time in a sealed state. After 2 weeks of storage, the freeze-dried patch was taken out and immersed in a 37°C PBS aqueous solution. The dry patch was able to quickly absorb water within 5 minutes and reform into a Janus hydrogel patch with single-sided adhesion properties ( Figure 7 b) Peel strength of the water-adhesive Janus hydrogel patch after 24 hours of adhesion to wet pig skin surface ( Figure 7 c) The peel strength is close to that of the Janus hydrogel patch before freeze-drying. These results show that the Janus hydrogel patch provided by the present invention has the characteristics of being freeze-dried and stored, being sticky when exposed to water, and being easy to use.
[0051] Experimental Example 5 Cytotoxicity Test of Janus Hydrogel Patch
[0052] Cell Counting Kit-8 (CCK-8) cell experiment: 200 mg of Janus hydrogel patch was placed in a PBS aqueous solution at 37°C for 24 hours to obtain a saturated leaching solution of the Janus hydrogel patch, and its mass concentration was set to 100%. The saturated leaching solution with a mass concentration of 100% was diluted with a blank PBS aqueous solution to a Janus hydrogel patch leaching solution with a mass concentration of 50%, 25%, 12.5%, 6.25%, 3.13%, and 1.56%. After culture and digestion, 3T3 fibroblasts were suspended in Dulbecco's modified Eagle medium (DMEM) containing 10% fetal bovine serum, and the concentration of 3T3 fibroblasts was adjusted to about 3000 / 100 μl. 100 μl of 3T3 fibroblast solution was added to the holes of a 96-well plate and cultured at 37°C and 5% CO2 for 12 hours. Subsequently, 90 μL of DMEM medium and 10 ul of Janus hydrogel patch extract of different mass concentrations were added to the above cultured 3T3 fibroblast solution. After 24 hours of continuous culture, the original culture medium was discarded, and 90 μL of new DMEM medium and 10 ul of Cell Counting Kit-8 reagent (CCK-8) were added, and the culture was continued for 1.5 hours. Finally, the absorbance of the solution sample in each well of the 96-well plate was detected at a wavelength of 450 nm, and the cell survival rate was calculated according to the formula: Cell survival rate = [(As-Ab) / (Ac-Ab)] × 100%. (As: absorbance of the experimental well; Ac: absorbance of the control well; Ab: absorbance of the blank well)
[0053] Cell fluorescence staining experiment: First, add the cultured 3T3 cells to a 12-well cell culture plate, with about 20,000 cells per well, and culture for 12 hours at 37°C and 5% CO2. Secondly, add 900μl DMEM culture medium and 100μl 100% mass concentration of Janus hydrogel patch saturated leaching solution to the above cultured 3T3 fibroblast solution, and continue to culture for 24, 48, and 72 hours. Subsequently, add 2μl of 1mM molar concentration of Calcein-AM reagent (Calcein-Am) and 4μl of 1mM molar concentration of propidium iodide (PI) reagent to the culture solution at different culture time points above, and incubate at 37°C for 20 minutes to perform fluorescence staining on the cells. Finally, take the stained samples and observe the cell morphology and fluorescence color under a confocal fluorescence microscope.
[0054] Cytotoxicity evaluation of Janus hydrogel patch: CCK-8 cytotoxicity test results ( Figure 8) showed that after 24h of co-culture of 3T3 fibroblasts with different mass concentrations of Janus hydrogel patch extracts, the cell survival rate was higher than 85%. The live-dead cell fluorescence staining experiment (Figure 9) showed that after 24h, 48h, and 72h of co-culture of 3T3 fibroblasts with 100% mass concentration of Janus hydrogel patch saturated extract, the growth morphology of 3T3 fibroblasts was normal, and the fluorescence color of most cells was green. The above cell experiments show that Janus hydrogel patch has good cell compatibility.
[0055] Example 2 Adjusting the mass of genipin in the hydrogel substrate layer
[0056] As described in Example 1, other conditions remain unchanged. In the process of preparing the gelatin-negatively modified zein-genipin hydrogel substrate layer, the mass of the genipin powder is changed from the original 3.6 mg to 7.2 mg to prepare the gelatin-negatively modified zein-genipin hydrogel substrate layer. Polylysine solution, negatively modified zein aqueous solution, and genipin solution are sprayed alternately on one side of the hydrogel substrate, and the excess solution is rinsed with double distilled water after each spraying, and dried with a nitrogen stream. After 8 cycles of spraying, a Janus hydrogel patch with single-sided adhesion behavior is obtained. The resulting Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0057] Example 3 Adjusting the mass of genipin in the hydrogel substrate layer
[0058] As described in Example 1, other conditions remain unchanged. In the process of preparing the gelatin-negatively modified zein-genipin hydrogel substrate layer, the mass of the genipin powder is changed from the original 3.6 mg to 1.8 mg to prepare the gelatin-negatively modified zein-genipin hydrogel substrate layer. Polylysine solution, negatively modified zein aqueous solution, and genipin solution are sprayed alternately on one side of the hydrogel substrate, and the excess solution is rinsed with double distilled water after each spraying, and dried with a nitrogen stream. After 8 cycles of spraying, a Janus hydrogel patch with single-sided adhesion behavior is obtained. The resulting Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0059] Example 4 Adjusting the mass of genipin in the hydrogel substrate layer
[0060] As described in Example 1, other conditions remain unchanged. In the process of preparing the gelatin-negatively modified zein-genipin hydrogel substrate layer, the mass of the genipin powder is changed from the original 3.6 mg to 0.6 mg to prepare the gelatin-negatively modified zein-genipin hydrogel substrate layer. Polylysine solution, negatively modified zein aqueous solution, and genipin solution are sprayed alternately on one side of the hydrogel substrate, and the excess solution is rinsed with double distilled water after each spraying, and dried with a nitrogen stream. After 8 cycles of spraying, a Janus hydrogel patch with single-sided adhesion behavior is obtained. The resulting Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0061] Example 5 Adjusting the concentration of the genipin solution in the adhesive layer
[0062] As described in Example 1, other conditions remain unchanged. When preparing the Janus hydrogel patch adhesive layer, the mass concentration of the genipin aqueous solution is changed from the original 1.0 mg / ml to 0.25 mg / ml. The same steps and spraying sequence are used. After repeated spraying for 8 cycles, a Janus hydrogel patch with single-sided adhesion behavior is obtained. The obtained Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0063] Example 6 Adjusting the concentration of the genipin solution in the adhesive layer
[0064] As described in Example 1, other conditions remain unchanged. When preparing the Janus hydrogel patch adhesive layer, the mass concentration of the genipin aqueous solution is changed from the original 1.0 mg / ml to 1.25 mg / ml. The same steps and spraying sequence are used. After repeated spraying for 8 cycles, a Janus hydrogel patch with single-sided adhesion behavior is obtained. The obtained Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0065] Example 7 Adjusting the concentration of the genipin solution in the adhesive layer
[0066] As described in Example 1, other conditions remain unchanged. When preparing the Janus hydrogel patch adhesive layer, the mass concentration of the genipin aqueous solution is changed from the original 1.0 mg / ml to 0.75 mg / ml. The same steps and spraying sequence are used. After repeated spraying for 8 cycles, a Janus hydrogel patch with single-sided adhesion behavior is obtained. The obtained Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0067] Example 8 Adjusting the number of spray cycles of the adhesive layer
[0068] As described in Example 1, other conditions remain unchanged. When preparing the Janus hydrogel patch adhesive layer, the number of repeated spraying cycles is changed from 8 times to 4 times, and a Janus hydrogel patch with single-sided adhesion behavior is obtained. The obtained Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0069] Example 9 Adjusting the number of spray cycles of the adhesive layer
[0070] As described in Example 1, other conditions remain unchanged. When preparing the Janus hydrogel patch adhesive layer, the number of repeated spraying cycles is changed from 8 to 20 times, and a Janus hydrogel patch with single-sided adhesion behavior is obtained. The obtained Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0071] Example 10 Adjusting the concentration of zein in the negatively charged modified zein solution
[0072] As described in Example 1, other conditions remain unchanged. In the process of preparing the gelatin-negatively modified zein-genipin hydrogel substrate layer, the mass concentration of negatively modified zein was changed from the original 75 mg / ml to 10 mg / ml to prepare the gelatin-negatively modified zein-genipin hydrogel substrate layer. Polylysine solution, negatively modified zein aqueous solution, and genipin solution were sprayed alternately on one side of the hydrogel substrate, and the excess solution was rinsed with double distilled water after each spraying, and dried with a nitrogen stream. After 8 cycles of spraying, a Janus hydrogel patch with single-sided adhesion behavior was obtained. The resulting Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0073] Example 11 Adjusting the concentration of zein in the negatively charged modified zein solution
[0074] As described in Example 1, other conditions remain unchanged. In the process of preparing the gelatin-negatively modified zein-genipin hydrogel substrate layer, the mass concentration of negatively modified zein was changed from the original 75 mg / ml to 150 mg / ml to prepare the gelatin-negatively modified zein-genipin hydrogel substrate layer. Polylysine solution, negatively modified zein aqueous solution, and genipin solution were sprayed alternately on one side of the hydrogel substrate, and the excess solution was rinsed with double distilled water after each spraying, and dried with a nitrogen stream. After 8 cycles of spraying, a Janus hydrogel patch with single-sided adhesion behavior was obtained. The resulting Janus hydrogel patch exhibits effective adhesion properties to different solid substrates and biological tissues.
[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A Janus hydrogel patch composed of protein and peptide, characterized in that: A substrate layer and an adhesive layer are sequentially provided from bottom to top; The substrate layer is formed by mixing and stirring a negatively charged modified corn protein solution and a gelatin aqueous solution to form a mixed solution through electrostatic and / or hydrogen bonding, and then covalently cross-linking and assembling genipin powder; The adhesive layer is formed by spraying polylysine aqueous solution, negatively charged modified corn protein solution and genipin aqueous solution in sequence and in equal volumes layer by layer for 6-8 times through electrostatic and / or hydrogen bonding covalent cross-linking; The substrate layer and the adhesive layer are bonded by electrostatic and hydrogen bonds between the corn protein solution, the gelatin aqueous solution and the polylysine aqueous solution, and are stably bonded by covalent cross-linking assembly through the genipin aqueous solution.
2. A Janus hydrogel patch composed of protein and polypeptide according to claim 1, characterized in that: The mass concentration of gelatin in the gelatin aqueous solution is 10-150 mg / ml; the mass concentration of corn protein in the negatively charged modified corn protein solution is 10-150 mg / ml; the mass concentration of polylysine in the polylysine aqueous solution is 1.28-64 mg / ml; the mass concentration of genipin in the genipin aqueous solution is 0.25-1.25 mg / ml.
3. The Janus hydrogel patch composed of protein and polypeptide according to claim 2, characterized in that: The volume ratio of the negatively charged modified corn protein solution to the gelatin aqueous solution in the substrate layer is 1:3, and the amount of genipin used is 0.2-2% of the mass fraction of the mixed solution.
4. A method for preparing a Janus hydrogel patch composed of protein and polypeptide according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing the genipin aqueous solution, gelatin aqueous solution, and negatively charged modified corn protein solution in the substrate layer in proportion, heating and stirring until a blue viscous liquid is formed and casting into a mold, and cooling naturally at room temperature to obtain a hydrogel substrate layer; (2) The polylysine aqueous solution, the negatively charged modified zein aqueous solution, and the genipin aqueous solution in the adhesion layer are sprayed layer by layer alternately onto one side of the substrate layer prepared in step (1) to obtain a Janus structure hydrogel patch.
5. The method for preparing a Janus hydrogel patch composed of protein and polypeptide according to claim 4, characterized in that: The preparation method of the negatively charged modified corn protein solution in step (1) is: adding corn protein to a sodium dodecyl sulfate aqueous solution to obtain a negatively charged modified corn protein aqueous solution.
6. The method for preparing a Janus hydrogel patch composed of protein and polypeptide according to claim 4, characterized in that: The stirring in step (1) is magnetic stirring, the stirring temperature is 20-80° C., the stirring time is 10-60 min, and the magnetic stirring speed is 100-800 r / min.
7. The method for preparing a Janus hydrogel patch composed of protein and polypeptide according to claim 4, characterized in that: In step (2), the pH values of the polylysine aqueous solution and the negatively charged modified zein aqueous solution are first adjusted to 5.0-8.0, and then the adhesion layer is prepared.